Developing Pancasila Learning Strategies through Culture-Based Interactive Media in Elementary Schools - Bustomi, Abu Amar; Khosiah, Nur; Fathurrohman, Amang (Assyfa Learning Journal, 2025)
This study examines the effectiveness of interactive culture-based media in enhancing cooperation and respect for diversity among elementary school students in Pancasila Education. Utilizing the ADDIE model for Research and Development, 45 students and 2 teachers in a rural setting participated over 10 weeks. The intervention included digital applications and local cultural activities integrated into the curriculum. Data were gathered through observations, interviews, and surveys and were analyzed using qualitative and inferential statistical methods. Results indicated a 35% improvement in cooperation and a 20% increase in cultural understanding compared to traditional methods. The dynamic interactions fostered a harmonious learning environment. Challenges included adapting materials to local contexts and providing teacher training. The study suggests developing sustainable training modules and adaptable learning aids, highlighting interactive media’s potential to enrich Pancasila Education. Further research is recommended to assess long-term impacts and broader educational applications.